Experimental Study of The Influence of The Addition Latex in Asphalt Concrete Over Stability - Wijaya, Evan; Darren, Jerry Jeremia; Antonius, David; ., Rachmansyah (Teknik dan Ilmu Komputer, 2016)
AbstrakÃÂ Perkerasan lentur merupakan komponen pendukung infrastruktur jalan dan banyak diperlukan pada jalan di Indonesia. Perkerasan lentur yang memiliki daya tahan yang baik sangatlah diperlukan. Bahan aditif Lateks merupakan bahan aditif yang memiliki karakteristik yang baik dalam ketahanan dan kelenturan. Penelitian ini dilakukan dengan menguji pengaruh kadar aspal optimal 5,33% terhadap penambahan lateks sebesar 15%, 20%, dan 25% dimana masing-masing dibuat lima benda uji. Pelaksanaan pengujian aspal ini dilakukan pada Laboratorium Jalan Raya Teknik Sipil Ukrida dengan tahapan pelaksanaan persiapan benda uji, pembuatan benda uji, dan pengujian Marshall. Berdasarkan hasil uji marshall, benda uji direndam selama 30 menit dengan suhu 60ÃÂºC. Dari hasil uji didapatkan hasil stabilitas tertinggi, yaitu 1.354,23 dengan kenaikannya terhadap spesifikasi sebesar 35,42% dengan flow-nya 5,30 mm meningkat 76,67%. Kenaikan stabilitas dan flow secara optimum berada pada kadar lateks 25%. Namun kadar lateks optimum berdasarkan keseluruhan parameter adalah 21,25%.ÃÂ Kata kunci: campuran aspal, aditif, lateks, stabilitasÃÂ ÃÂ AbstractÃÂ Highway pavements are supporting a long-run economic growth. The economic growth also demands comfortable and safe access, but the comfortable aspect cannot be obtained if pavements are incompatible. Therefore, pavements are still being developed according to needs in several cases. The addition of latex on its pavement layer is one of the developments. Latex is one of the substances used for high strength materials with a high degree of elasticity. The mixture of latex with asphalt may result in the increase of pavementÃ¢â¬â¢s stability to support heavy loads of vehicles and puddles that occur due to high rainfall every year in Indonesia. This research is conducted at UKRIDA Civil Engineering Laboratory of Highway Engineering with steps as follows: preparations, the manufacture of samples, and Marshall Test. According to Marshall Test, specimens were soaked for 30 minutes with temperature as high as 60ÃÂºC. The highest stability value is obtained at 1354.23 with an increase towards all specifications at 35,42% and flow value atÃÂ  5,30 mm (a 76,67%. Increase). The increase of stability and flow value is optimal with latex composition at 25%. However, the optimal percentage of latex according to all parameters is 21.25%.ÃÂ Keywords: asphalt mixture, additive, latex, stability